An Up-to-date Meta-analysis of Coffee Consumption and Risk of Prostate Cancer - Xia, Jiadong; Chen, Jie; Xue, Jian-Xin; Yang, Jie; Wang, Zeng-Jun (Urology Journal, 2017)
Purpose: Results of the association between coffee consumption (CC) and the risk of prostate cancer (PC) are still controversy. Based on published relevant studies, we conducted an up-to-date meta-analysis to investigate this issue. Materials and Methods: The protocol used in this article is in accordance with the PRISMA checklist. Eligible studies were screened and retrieved by using PUBMED and EMBASE as well as manual review of references up to July 2016. We calculated the pooled relative risk (RR) with 95% confidence interval (CI) with random effect models. The dose-response relationship was assessed by generalized least-squares trend estimation analysis. Results: Totally, we included twenty-eight studies (14 case-control and 14 cohort studies) on CC with 42399 PC patients for the final meta-analysis. No significant association of PC was found for high versus non/lowest CC, with RR = 1.07 (95% CI: 0.96-1.18). In subgroup meta-analysis by study design, there were no significant positive associations between CC and PC in case-control studies (RR = 1.19, 95% CI: 1.05-1.35) or in the cohort studies (RR = 0.97, 95% CI: 0.84-1.12). Additionally, RR with different quality of studies were respectively 1.15 (95% CI: 0.99-1.34) and 1.28 (95% CI: 1.03-1.58) for high and low quality in the case-control studies; while were respectively 1.02 (95% CI: 0.88-1.20) and 0.81 (95% CI: 0.57-1.14) in the cohort studies. When analyzed by geographic area, we found no association between CC and PC, with RR = 1.06 (95% CI: 0.86-1.30) for 10 studies from Europe, 1.06 (95% CI: 0.94-1.20) for 13 studies conducted in America; 1.12 (95% CI: 0.70-1.79) for 4 studies from Asia. However, in subgroup analysis by subtype of the disease, there was a significant negative (beneficial) association in the localized PC (RR = 0.90, 95% CI: 0.84-0.97), but not for the advanced PC (RR = 0.90, 95% CI: 0.70-1.16). Additionally, RR = 0.99 (95% CI: 0.98-0.99) for an increment of one cup per day of coffee intake shows significant association with the localized PC. Conclusion: Our results indicate that CC has no harmful effect on PC. On the contrary, it has an effect on reducing the localized PC risk. Further prospective cohort studies of high quality are required to clarify this relationship.